2014
DOI: 10.1007/s10802-014-9928-z
|View full text |Cite
|
Sign up to set email alerts
|

Why Wait? The Effect of Wait-Times on Subsequent Help-Seeking Among Families Looking for Children’s Mental Health Services

Abstract: Placement on a wait-list may increase families' help-seeking efforts, leading them to contact more than one children's mental health (MH) agency/professional. Two issues were examined in the current study: 1) Does time on a wait-list for families impact the time to contact a new agency for children's MH services? 2) What are the effects of predisposing (e.g., child age), need (e.g., child psychopathology), and enabling/system-level factors (e.g., parent treatment history) on the length of time parents wait bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…In line with previous studies, there was a high level of heterogeneity in waiting times. [13][14][15][16][17][18][19] We found shorter waiting times than reported in a recent child and adolescent mental health surveyin the present study, 16 737 (78%) young people waited less than 10 weeks, 3902 (18%) waited between 10 weeks and 6 months, and 780 (4%) waited more than 6 monthsalthough it should be noted that different methodologies including operationalisations of waiting times were used. 20 The hypothesis that young people with more severe problems would have shorter waiting times for mental health services than young people with less severe problems was supported.…”
Section: Main Findings and Comparison With Findings From Other Studiessupporting
confidence: 48%
See 1 more Smart Citation
“…In line with previous studies, there was a high level of heterogeneity in waiting times. [13][14][15][16][17][18][19] We found shorter waiting times than reported in a recent child and adolescent mental health surveyin the present study, 16 737 (78%) young people waited less than 10 weeks, 3902 (18%) waited between 10 weeks and 6 months, and 780 (4%) waited more than 6 monthsalthough it should be noted that different methodologies including operationalisations of waiting times were used. 20 The hypothesis that young people with more severe problems would have shorter waiting times for mental health services than young people with less severe problems was supported.…”
Section: Main Findings and Comparison With Findings From Other Studiessupporting
confidence: 48%
“…There is a high level of heterogeneity in waiting times reported in previous studies. [13][14][15][16][17][18][19] A recent child and adolescent mental health survey in England found that 61% of those with a mental health problem accessed specialist services in less than 10 weeks, 18% in 10 weeks to 6 months, and 21% in more than 6 months. 20 Examining waiting times is complex given the number of environmental and individual characteristics related to mental health, help-seeking behaviour and service provision.…”
Section: Factors Linked To Waiting Timesmentioning
confidence: 99%
“…Long wait lists for access to psychiatrist consultation place constraints on specialists' time and ability to adequately perform metabolic monitoring; this necessitates fragmented physical care and places patients who are at risk for undetected cardiometabolic complications (Brown et al 2002;Cohn & Sernyak 2006;Pringsheim et al 2011a;Schraeder & Reid 2015). Long wait lists for access to psychiatrist consultation place constraints on specialists' time and ability to adequately perform metabolic monitoring; this necessitates fragmented physical care and places patients who are at risk for undetected cardiometabolic complications (Brown et al 2002;Cohn & Sernyak 2006;Pringsheim et al 2011a;Schraeder & Reid 2015).…”
Section: Challenges Associated With Meta-bolic Monitoringmentioning
confidence: 99%
“…Uptake of metabolic monitoring guidelines and the overall quality of care offered to children and adolescents using SGAs are influenced by how Canadian psychiatric services are currently being delivered. Long wait lists for access to psychiatrist consultation place constraints on specialists' time and ability to adequately perform metabolic monitoring; this necessitates fragmented physical care and places patients who are at risk for undetected cardiometabolic complications (Brown et al 2002;Cohn & Sernyak 2006;Pringsheim et al 2011a;Schraeder & Reid 2015). There are limited Canadian data on youth outpatient psychiatry service use and wait times (Canadian Association of Paediatric Health Centres & Youth Mental & Health Consortium Advisory 2010).…”
Section: Challenges Associated With Meta-bolic Monitoringmentioning
confidence: 99%
“…age, gender and social deprivation). Yet, it is clear that waiting can lead to families of CYP seeking help from other sources (Schraeder & Reid, ), but we do not know whether these alternative sources are appropriate. Moreover, we do not know if those who wait without recourse to seeking help from other sources actually get support while waiting.…”
Section: Introductionmentioning
confidence: 99%